2016
DOI: 10.3892/br.2016.772
|View full text |Cite
|
Sign up to set email alerts
|

Organic cation transporter 6 directly confers resistance to anticancer platinum drugs

Abstract: Abstract. Organic cation transporters (OCTs) of the solute carrier family 22 have a critical role in the cellular uptake of anticancer platinum drugs. Recently, we found that a decreased OCT6 expression is associated with a reduced intracellular uptake of cisplatin (CDDP), and concomitant resistance to CDDP. In the present study, we examined whether OCTs directly confer resistance to another platinum drug, oxaliplatin (L-OHP). To address this, we used parental lung cancer cell lines, PC-14 and SBC3; L-OHP-resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…12,13 Copper transporters are involved in the accumulation of oxaliplatin, 14 and the expression levels of organic cation transporters (OCT) positively correlate with oxaliplatin absorption and resistance. 15,16 ABC transporters, such as multidrug resistance proteins (MRPs) and sodium potassium ATPases, are also involved in oxaliplatin drug resistance. [17][18][19][20] (iii) Glutathione (GSH)-mediated oxaliplatin effusion reduces the amount of oxaliplatin in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Copper transporters are involved in the accumulation of oxaliplatin, 14 and the expression levels of organic cation transporters (OCT) positively correlate with oxaliplatin absorption and resistance. 15,16 ABC transporters, such as multidrug resistance proteins (MRPs) and sodium potassium ATPases, are also involved in oxaliplatin drug resistance. [17][18][19][20] (iii) Glutathione (GSH)-mediated oxaliplatin effusion reduces the amount of oxaliplatin in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Distinct cellular accumulation pathways may possibly confer some tumor selectivity on these non‐specific cytotoxics. The influence of copper transporters (hCTR) and organic cation transporters (OCT) on platinum uptake even varies amongst the three clinically approved agents . Furthermore, hOCT transport is implicated in the kidney toxicity associated with cisplatin but not oxaliplatin or carboplatin .…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that organic cation transporter 6 (OCT6) is a mediator of platinum influx into cancer cells, and down-regulation of OCT6 is one mechanism of acquired platinum resistance in lung cancer (6), as it is with other platinum derivatives (7). Single nucleotide polymorphisms (SNPs) are the most common type of genetic variation.…”
Section: Abstract Background: Organic Cation Transportermentioning
confidence: 99%